(untitled) (Abstracta, 2022)
Artigos publicados - P034-2022 à P076-2022 Correções - C001-2022 à C002-2022 Defesas de Dissertações do IFGW - D003-2022 à D005-2022 Defesas de Teses do IFGW - T004-2022 à T008-2022